PERTANGGUNGJAWABAN PIDANA PELAKU KEJAHATAN PERKOSAAN TERHADAP LAKI-LAKI - Pratiwi Dharayanti, Desak Made; Sri Indrawati, A. A. (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015)
The paper is titled " Criminal Responsibility Offenders Rape of Men " . The problems discussed regarding the rape of men and accountability of the crime of rape against men . The method used in this paper is the normative study . Article 285 of the Criminal Code only mentions of rape against women only and not to men . There is no clear regulations on rape committed by men and women with male victims and in case of rape against men used Article 289 of molestation . Meaning molestation act is against sexual shame . The element of abuse of Article 289 that a person by force or threat of violence ; force ; perform or tolerate obscene acts . The conclusion that there are no clear regulations on rape victims were male and accountability of the crime of rape against men used Article 289 of molestation.
Keywords: Criminal responsibility, rape of men